EIB Working Paper 2022/12 - Determinants of the exchange rate, its volatility and currency crash risk in Africa's low and lower middle-income countries - Okot, Anjelo (European Investment Bank, 2022)
"The last three decades have witnessed substantial changes in the foreign exchange markets in Africa, with moves towards liberalisation and flexible exchange rate regimes. This has increased the influence of financial market conditions and heightened the risk of exchange rate volatility and large and sudden exchange rate movements. This paper investigates the determinants of nominal exchange rates, their volatility, and crash risk in African lower and lower-middle income countries. It combines macro-panel estimations for 15 such countries with insights from interviews with market participants. It shows the importance of these countries' distinctive export structure, concentrated in a few agricultural and mineral-based commodities, as well as recent financial integration, for exchange rate determination. It finds that terms of trade, export concentration, and export prices have a significant impact on the exchange rate level and volatility. By contrast, financial factors including the interest rate differential, international market conditions, and short-term financial flows, influence the likelihood of sudden and large exchange rate movements."